Association of physical therapy techniques can improve pain and urinary symptoms outcomes in women with bladder pain syndrome. A randomized controlled trial - Hacad,Claudia Rosenblatt (2022)
ABSTRACT Purpose: to verify the effects of biofeedback (BF) and manual therapy (MT) associated with transcutaneous electrical nerve stimulation (TENS) or postural exercises (PE) in the treatment of bladder pain syndrome (BPS) in women regarding pain and urinary symptoms. Materials and Methods: a parallel-randomized controlled trial was conducted in BPS patients diagnosed according to NIH clinical criteria. Two specialized physiotherapists applied demographic and validated questionnaires of perineal and suprapubic pain (VAS), urinary symptoms and problems (ICSI and ICPI) and sexual function (FSFI) and a physical assessment was made to identify myofascial trigger points. Thirty-one women, mean age 51.8 ± 10.9 were randomized in three groups of treatment consisting of ten weekly sessions of BF and MT (Conventional group); BF, MT, and TENS (TENS group); and BF, MT, and PE (Postural group). Results: Postural group improved perineal and suprapubic pain after treatment (p<0.001 and p=0.001, respectively), and the suprapubic pain improvement remained persistent at 3 months of follow up (p=0.001). Postural group improved urinary symptoms and problems after treatment (p<0.001 and p=0.005, respectively) and during follow up (p<0.001 and p=0.001). Conclusions: Biofeedback and manual therapy associated with postural exercises showed a significant improvement in perineal and suprapubic pain and urinary symptoms after treatment and during follow-up. Both results suggest a possible role for the use of this physiotherapy technique to treat BPS patients. Longer follow-up and a larger number of patients are necessary to confirm these conclusions.